Bacteriocin and antibiotic resistance plasmids in Bacillus cereus and Bacillus subtilis. - Bernhard, K (1978)
A number of plasmids have been isolated as covalently closed circular DNAs from strains of Bacillus cereus and B. subtilis. From 12 out of 15 strains of B. cereus, plasmids could be isolated. Most of the B. cereus strains contained two or more plasmids. Their molecular weights ranged from 1.6 X 10(6) to 105 X 10(6). Bacteriocin production could be attributed to a 45 X 10(6)-dalton plasmid (pBC7) from B. cereus DSM 336, and tetracycline resistance to a 2.8 X 10(6) plasmid (pBC16) from B. cereus GP7. Two streptomycin-resistant strains of B. subtilis harbored plasmids of 5.2 X 10(6) and 9 X 10(6), respectively, which were, however, not correlated with the antibiotic resistance. The plasmid carrying resistance to tetracycline, pBC16, which was originally isolated from B. cereus, could be subsequently transformed in B. subtilis, where it is stably maintained.